(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to determine the improvement of students’ ability to understand mathematical concepts by using the Realistic Mathematics Approach (PMR). This study is a pseudo-experimental research with posttest only control group design. The population of this study is all students of grade XI SMK Negeri 6 Medan even semester of the 2025 school year with a total of 280 students and distributed into 8 classes. The sample of this study is class X Accounting 1 with a total of 36 students as an experimental class and class X Accounting 2 with a total of 35 students as a control class. Data were collected using tests and statistically analyzed to find out the differences between the two classes. The results of the hypothesis test with the Mann Whitney U test, it is known that the value of Z-count = 1.879 is more than Z-critical = 1.645. This shows that the median concept understanding of students who follow learning with the PMR Approach is higher than the median concept understanding that follows regular learning. The average value of students’ concept understanding in the class applying the PMR approach x ̅=62 was higher than the class that followed the usual learning where x ̅=53. Thus, it can be concluded that the understanding of mathematical concepts of students who participate in learning with the PMR approach is higher than the understanding of mathematical concepts of students who follow ordinary learning